Decomposition of sugarcane straw collected at different rates after mechanical harvest - Ramos, Nilza Patrícia (2016)
The objective of this work was to determine the effect of collecting different levels of sugarcane straw on its decomposition on soil surface, after consecutive ratoons. The trial was conducted for two consecutive ratoons, using the sugarcane variety RB845210, testing four amounts of remaining straw after harvest: 11.3, 8.5, 5.7, and 2.8 Mg ha-1. Decomposition rates of biomass, carbon, nitrogen, cellulose, hemicellulose, and lignin were evaluated, as well as the C/N ratio and the mineralized quantities of C and N from the straw. Thedistinct levels of sugarcane straw aboveground do not alter decomposition rates, neither do they alter the mineralization of carbon, hemicellulose, cellulose, and lignin within the same ratoon. The straw decomposition process persists along the two ratoon cycles, regardless of the initial amount of straw on soil surface. The C/N ratio and lignin decay are adequate indicators for detecting differences of straw decomposition rates between the evaluated levels of straw, while hemicellulose and cellulose decay detects only differences in rates over time. In absolute terms, the lower the initial aboveground straw level, the higher the amounts of carbon and nitrogen mineralized, even if there are no differences in decomposition rates.